RANCANG BANGUN PENGOLAH PAKAN OTOMATIS SUGAR GLIDER BERBASIS INTERNET OF THINGS - Dinarti Maharani; Syamsul Bahri; Suhardi Suhardi (Coding Jurnal Komputer dan Aplikasi, 2022)
Sugar gliders are nocturnal, which means they are active at night. Sugar Glider food ingredients use SUN brand cereal milk. The dose of feed for 1 meal is 6 grams of powder and 8 ml of water. To provide food on time, a tool is needed that can perform processing and feeding in the Sugar Glider cage automatically and the status is monitored through the website interface. The components used are ultrasonic sensors, mini DC water pumps, servo motors, DC motors. The results of ultrasonic sensor readings on the sensor nodes are monitored through the website interface. The Sugar Glider automatic feed processor design applies the concept of Internet of Things (IoT) technology, namely data communication using a wireless network (without cables). The hardware is built using two nodes, namely the sensor node as a monitor for the stock of feed ingredients in the tank and the controller node as a feed processor based on an active schedule. Testing of feed processing automatically on the controller node starts from the request for schedule status data to the server. The processing of feed based on the schedule entered on the website was successfully carried out by the system. The system succeeded in removing feed powder with an average value of 5.8 grams of powder coming out close to 6 grams and removing water with an average value of 8.4 ml approaching 8 ml. Testing of data transmission has been successfully carried out and the data is displayed on the website in real time.